Determinants of Regional Own-Source Revenue (PAD) and Its Implications for Local Budget Capacity: Evidence from Nduga Regency, Indonesia - Kamius Gwijangge; Elsyan R. Marlissa; Transna Putra Urip S (International Journal of Accounting and Management Information Systems, 2026)
Purpose: This study analyzes the development and performance of Regional Own-Source Revenue (PAD), identifies structural and institutional factors causing its persistently low and unstable levels, and examines its implications for the Regional Revenue and Expenditure Budget (APBD) structure in Nduga Regency, Papua Highlands Province, Indonesia. Research Methodology: This study used a quantitative approach with a descriptive and explanatory design. Secondary time-series data were obtained from official regional financial reports, including LRA, APBD, and BPKAD documents for 2022–2024. Data were analyzed using multiple linear regression with SPSS, supported by classical assumption tests, t-tests, F-tests, and the coefficient of determination. Results: The findings PAD in Nduga Regency remains low, with an average of IDR 4.24 billion, negative growth of -1.05%, and a fiscal independence ratio below 5% of total regional revenue. Regression results indicate that economic capacity, transfer fund dependency, and governance quality significantly affect PAD, while geographic and infrastructure conditions show a weaker effect. The model explains 61.2% of PAD variance. Conclusions: Low PAD in Nduga Regency is mainly influenced by weak economic capacity, high dependence on central transfers, limited governance quality, and geographic constraints. Therefore, an integrated strategy is needed through local economic development, governance reform, infrastructure improvement, and the redirection of funds toward productive investments. Limitations: This study is limited by its three-year observation period, the use of proxy variables, and its focus on a single region, which may restrict generalizability. Contributions: This study provides insights into PAD determinants and offers policy recommendations to strengthen regional fiscal capacity.